2011
DOI: 10.1136/annrheumdis-2011-200170
|View full text |Cite
|
Sign up to set email alerts
|

Sustained inhibition of progressive joint damage with rituximab plus methotrexate in early active rheumatoid arthritis: 2-year results from the randomised controlled trial IMAGE

Abstract: BackgroundIn the IMAGE study, rituximab plus methotrexate (MTX) inhibited joint damage and improved clinical outcomes at 1 year in MTX-naïve patients with early active rheumatoid arthritis.ObjectiveThe aim of this study was to assess joint damage progression and clinical outcomes over 2 years.MethodsPatients (n=755) were randomised to receive rituximab 2×500 mg+MTX, 2×1000 mg+MTX or placebo+MTX. The placebo-controlled period continued to week 104. Two-year end points were defined as secondary or exploratory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 24 publications
3
69
0
7
Order By: Relevance
“…Another validated approach in human RA is anti-B cell (anti-CD20) mAb therapy, which is administered primarily to anti-TNF non-responders (Tak et al, 2012). Although anti-CD20 treatment has not been tested specifically in animal models, B cell deletion or depletion is known to protect against arthritis (Svensson et al, 1998;Yanaba et al, 2007) and anti-CD19 mAb therapy was found to effective in CIA, without depleting B cells (Cemerski et al, 2010).…”
Section: Comparison Of Drug Therapy In Ra and Animal Models (A) Biolomentioning
confidence: 99%
“…Another validated approach in human RA is anti-B cell (anti-CD20) mAb therapy, which is administered primarily to anti-TNF non-responders (Tak et al, 2012). Although anti-CD20 treatment has not been tested specifically in animal models, B cell deletion or depletion is known to protect against arthritis (Svensson et al, 1998;Yanaba et al, 2007) and anti-CD19 mAb therapy was found to effective in CIA, without depleting B cells (Cemerski et al, 2010).…”
Section: Comparison Of Drug Therapy In Ra and Animal Models (A) Biolomentioning
confidence: 99%
“…Most adverse events tar a artrite reumatoide (22)(23)(24). Estudos clínicos também evidenciaram que essas drogas são seguras (17,19,20 De acordo com um estudo denominado "IMAGE trial" (27,28), não incluído em nossas meta-análises por apresentar dados após 52 semanas de tratamento, mas delineado de forma a se encaixar nos demais critérios de inclusão do nosso estudo, aproximadamente 42 % dos pacientes usando placebo atingiram o ACR50, e 65 % dos pacientes usando rituximabe 1,0 g x 2 atingiram esse resultado. Isso significa que houve uma melhora dos pacientes considerando esse parâmetro clínico.…”
Section: Discussionunclassified
“…there was no difference between rituximabtreated patients and the control group. According to a large study called "IMAGE trial" (27,28), which was not included in our meta-analyses because it presents data after 52 weeks of treatment although it fits the other criteria, approximately 42 % of the patients on placebo achieved ACR50, and 65 % of the patients on rituximab 1,0 g x 2 achieved this parameter. This means that there was an improvement in this clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты крупномасштабных РКИ свиде-тельствуют о сходной эффективности двух инфузий РТМ в дозах 500 и 1000 мг [36][37][38][39][40][41][42][43][44][45][46] (табл. 3).…”
Section: таблицаunclassified
“…По критерию «non-inferiority» (эффективность/безо-пасность/переносимость метода лечения не ниже, чем у ак-тивного контроля) низкие дозы РТМ не уступают высоким дозам по ACR20, ACR50 и динамике DAS28 через 24 и 48 нед. Представляют интерес отдаленные результаты ис-следования IMAGE, согласно которым сходная эффектив-ность и безопасность низких и высоких доз РТМ сохраня-лись в течение 104 нед [44]. Достоверных различий разных доз РТМ в отношении подавления прогрессирования дест-рукции суставов по данным рентгенологического исследо-вания отмечено не было.…”
Section: таблицаunclassified